2016
DOI: 10.5851/kosfa.2016.36.6.787
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Kefir against Various Food Pathogens and Spoilage Bacteria

Abstract: Kefir is a unique fermented dairy product produced by a mixture of lactic acid bacteria, acetic acid bacteria, and yeast. Here, we compared the antimicrobial spectra of four types of kefirs (A, L, M, and S) fermented for 24, 36, 48, or 72 h against eight food-borne pathogens. Bacillus cereus, Staphylococcus aureus, Listeria monocytogenes, Enterococcus faecalis, Escherichia coli, Salmonella Enteritidis, Pseudomonas aeruginosa, and Cronobacter sakazakii were used as test strains, and antibacterial activity was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
58
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 19 publications
6
58
0
8
Order By: Relevance
“…This is an important result to note, since antimicrobial molecules often react differently at different pHs 30,31 . Thus, the power of kefir serum to kill bacteria is attributable not to a low pH but to antimicrobial molecules produced during fermentation, in corroboration with other studies that demonstrated that the antimicrobial activity of four different samples of kefir was not related to their low pH (between 3.65 and 4) 3 .…”
Section: Discussionsupporting
confidence: 88%
“…This is an important result to note, since antimicrobial molecules often react differently at different pHs 30,31 . Thus, the power of kefir serum to kill bacteria is attributable not to a low pH but to antimicrobial molecules produced during fermentation, in corroboration with other studies that demonstrated that the antimicrobial activity of four different samples of kefir was not related to their low pH (between 3.65 and 4) 3 .…”
Section: Discussionsupporting
confidence: 88%
“…The antimicrobial activity of kefir or its constituent microorganisms against various foodborne pathogens and spoilage bacteria has been reported previously [2,27]; however, the actual antimicrobial properties against cariogenic bacteria have not previously been demonstrated. LAB produce various antimicrobial compounds such as organic acids, hydrogen peroxide, diacetyl, and bactericidal polysaccharides or peptides [28].…”
Section: Discussionmentioning
confidence: 96%
“…These compounds could be implicated in the reduction of food borne pathogens and also in the treatment and prevention of gastroenteritis and vaginal infections (Leite et al, 2013). The antimicrobial activity of four kefirs types, fermented for 24-72 h against eight food-borne pathogens (Bacillus cereus, Staphylococcus aureus, Listeria monocytogenes, Enterococcus faecalis, Escherichia coli, Salmonella enteritidis, Pseudomonas aeruginosa and Cronobacter sakazakii) was revealed by spot method (Kim et al, 2016). The strongest antimicrobial spectrum was obtained after at least 36-48 h of fermentation for all kefirs.…”
Section: Antimicrobial Activitiesmentioning
confidence: 99%